Imaging spatial-temporal distribution of moisture in intact maize ear. (October 2022) - Li, Yang; Wang, Nan; Fan, Li-Feng; Wang, Yong-Qian; Zhao, Peng-Fei; Huang, Lan; Wang, Zhong-Yi
Highlights: EIT offers 3D distribution and changes of water in maize ear in situ at maturity. Internal conductivity varied with the moisture content in maize ear. Impedance spectrum extreme value was used for the characteristic frequency for excitation signal. The resilient electrode array can dynamically change with the growth of the maize ear. Abstract: The moisture distribution in maize ears during the growth period has a major impact on crop quality and post-harvest production costs and is an important indicator for plant breeding. An electrical impedance tomography system with a resilient electrode array was designed to fit around a maize ear, and featured an adjustable diameter that can be adapted to the growth of the ear. We used the system to monitor the dehydration of an intact maize ear in situ over 5 days and observe the changes in moisture distribution. The high-contrast images correlated with the moisture distribution in the maize ear. We also created a 3D model to visualize the distribution of moisture content within the maize ear. Our method provides a novel tool to monitor the spatial-temporal dynamics of the water content within the maize ear in situ.